UJI AKTIVITAS ANTIINFLAMASI KOMBINASI EKSTRAK DAUN SALAM (Syzygium polyanthum (Wight) Walp) dan EKSTRAK DAUN PEPAYA (Carica papaya L.) TERHADAP UDEMA KAKI TIKUS PUTIH JANTAN YANG DIINDUKSI KARAGENIN - Syahputra, Dhika Adhil; Samodra, Galih; Prabandari, Rani (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2022)
Inflammation or inflammation is the body's normal response to tissue damage caused by physical trauma, chemical and microbial damage. Plants that are thought to have anti-inflammatory properties are bay leaves (Syzygium polyanthum (Wight) Walp). Which acts as an anti-inflammatory in bay leaves and papaya leaves are flavonoids. Bay leaf and papaya leaf extracts were extracted using 70% ethanol by maceration method. The test animals were divided into 7 groups, namely a negative control group (Na CMC), a positive group (Diclofenac Sodium 50 mg), a single dose group of 100 mg/kgBW bay leaf extract, a single dose group of 100 mg/kgBW papaya leaf extract, and a combination group of leaf extracts. salam and papaya leaf extract 50mg/kgBB: 50mg/kgBB, 150mg/kgBB: 100mg/kgBB, 250mg/kgBB: 200mg/kgBB. Treatment 1 hour after the hind legs of rats was induced by subplantar carrageenin. The results showed that the combination of bay leaf and papaya leaf extracts had anti-inflammatory activity. The results of the calculation of the inflammatory power in the combination group showed inflammatory activity.